OCL-based Runtime Monitoring of JVM hosted Applications - Hamann, Lars; Gogolla, Martin; Kuhlmann, Mirco (Electronic Communications of the EASST, 2011)
In this paper we present an approach that enables users to monitor and verify the behavior of an application running on a virtual machine at the model level. Concrete implementations of object-oriented software usually contain a lot of technical classes. Thus, the central parts of an application, e.g., the business rules, may be hidden among peripheral functionality like user-interface classes or classes managing persistency. Our approach makes use of modern virtual machines and allows the devloper to profile an application in order to achieve an abstract monitoring and verification of central application components. We represent virtual machine bytecode in form of a so-called platform-aligned model (PAM) comprising OCL invariants and pre- and postconditions. In contrast to related work, our approach uses the original source or bytecode of the monitored application as it stands and does not require any changes. We show a prototype implementation as an extension of the UML and OCL tool USE. Also, we investigate the impact of our approach to the execution time of a monitored system.